Kebijakan Validasi Bea Perolehan Hak Atas Tanah dan Bangunan - Koko Sandro Okto Maulana; Budi Ispriyarso; Mujiono Hafidh Prasetyo (Notarius, 2021)
The object of the transfer of land and building rights is taxed from the side of the seller and the buyer. With regional autonomy, the authority to collect BPHTB is now in the hands of the regional government. This article examines the policy of the Tegal City Government regarding the imposition of obligations and responsibilities as well as the validation provisions of the Land and Building Rights Acquisition Fee to a notary/PPAT without hindering the land registration process. The research method used is normative juridical. The specification of the research used is descriptive-analytical. The data analysis technique used qualitative analysis. The results of the study indicate that the policy of the Tegal City Government towards the imposition of BPHTB validation obligations to a notary/PPAT is based on the Tegal City Regional Regulation. Taxpayers who do not know the tax calculation process fully entrust the notary/PPAT. The Tegal City Government has adopted a policy of imposing a validation obligation on BPHTB payments to a notary/PPAT. The responsibility of a notary/PPAT is only limited to submitting a request for validation of BPHTB that has been paid by the taxpayer before signing the deed of transfer of land rights.Keywords: Policy; Notary Public; ValidationAbstrakObyek pajak peralihan hak atas tanah dan bangunan dikenakan pajak dari sisi penjual dan pembeli. Adanya otonomi daerah maka wewenang pemungutan BPHTB kini berada di tangan pemerintah daerah. Artikel ini mengkaji kebijakan Pemda Kota Tegal terhadap pembebanan kewajiban dan tanggung jawab serta ketentuan validasi“Bea Perolehan Hak Atas Tanah dan Bangunan”kepada notaris/PPAT tanpa menghambat proses pendaftaran tanah.“Metode penelitian yang digunakan adalah yuridis normative.”Spesifikasi penelitian yang digunakan adalah deskriptifaanalitis.”Teknik analisis data menggunakan analisis secara kualitatif. Hasil penelitian menunjukkan bahwa kebijakan Pemda Kota Tegal terhadap pembebanan kewajiban validasi BPHTB kepada notaris/PPAT didasarkan pada Peraturan Daerah Kota Tegal.”Wajib pajak yang tidak mengetahui proses penghitungan pajak mempercayakan sepenuhnya kepada”notaris/PPAT. Pemda Kota Tegal mengambil kebijakan membebankan kewajiban validasi atas pembayaran BPHTB kepada notaris/PPAT. Tanggung jawab notaris/PPAT hanya sebatas menyampaikan permohonan validasi BPHTB yang telah dibayarkan wajib pajak sebelum menandatangani akta pemindahan hak atas tanah.Kata kunci: Kebijakan; Notaris; Validasi